Furthering Prostration in the Hebrew Bible: A Non-Denotative Analysis of hištaḥăwah - Smith, Andrew Christopher (Journal for the study of the Old Testament, 2017)
This article provides a non-denotative analysis of the Hebrew word for prostration in the Old Testament, hištaḥăwah. It does so in order to better grasp the discursive situating of prostration as a ritual within the socio-religious contexts and conceptions of biblical authors and peoples. The analysis of hištaḥăwah proceeds along non-denotative lines, specifically analyzing its usage as per its connotative attribution, its grammatical subjects and number (communal versus individual), and its directedness. This study shows that the usage of hištaḥăwah must be understood as a variegated literary term representing a ritualized action that originally was seen and understood multivalently. However, the aggregate usage of the term indicates continuities of understanding as well as changes due to historical circumstances and uses. Such measures give greater insight into experiential aspects of Israelite religious practice, as well as providing insight into the discursive norms that structured Israelite society and worldview during different periods